Reliability Level List Based Iterative SISO Decoding Algorithm for Block Turbo Codes - Sudharsan, V; Vijay Karthik, V; Yamuna, B (Telkomnika, 2018)
Simulation results show that the proposed algorithm has a clear advantage of performance improvement over conventional Chase-2 based SISO decoding scheme with reduced decoding latency at lower noise levels. The encoded block is passed to an interleaver and the interleaved code block is subsequently encoded using C2-the second encoding scheme. [...]for a message block of dimension k1 x k2, the turbo code T=C1 0 C2 can be obtained by: a. Encoding k1 rows using the coding scheme C2. b. Encoding k2 columns using the coding scheme C1. The output from the final iteration is taken as the optimal estimate of transmitted code block. 3.The proposed RLL Based Iterative Decoding Algorithm for Block Turbo Codes The main components of BTC based decoding scheme are an elementary decoder for each of the constituent block code and iterative SISO turbo decoding, where exchange of extrinsic information between iterations take place. The fact that the computational complexity of Chase-2 decoding algorithm remains the same even at a lower noise level has lead researchers to come up with modifications/alternate solutions to Chase-2.